Prenatal diagnosis of transposition-like double-outlet right ventricle with mitral valve atresia in heterotaxy syndrome - Theera Tongsong (2018)
We present a case of heterotaxy syndrome with right isomerism detected in a twin fetus, with the sonographic findings that established this diagnosis. At 24 weeks' menstrual age, ultrasound detected anomalies in the heart suggestive of heterotaxy syndrome. Intrauterine fetal echocardiography demonstrated that the heart of the affected twin was located on the left side with a normal cardiac axis. The right ventricle was much larger than the left ventricle. The appearance of the mitral valve was dysplastic with restricted motion. The ascending aorta exited from the right ventricle, anterior to, right to, and parallel to the smaller pulmonary trunk, which also arose from the right ventricle. Double-outlet right ventricle (DORV) was clearly demonstrated. Cesarean section was performed at 38 weeks' menstrual age. Both twins were healthy and survived. Postnatal echocardiography and MRI confirmed the prenatal findings. At the age of 4 months, the affected infant had no evidence of cardiac decompensation. This report shows that conventional ultrasound can be used to detect heterotaxy syndrome and that intrauterine fetal echocardiography can delineate the cardiac complex in heterotaxy syndrome. Postnatal surgery with complex Fontan procedures was planned for the affected twin. © 2005 Wiley Periodicals, Inc.